2020
DOI: 10.1016/j.annonc.2019.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Asian adapted ESMO Clinical Practice Guidelines for the management of patients with intermediate and advanced/relapsed hepatocellular carcinoma: a TOS–ESMO initiative endorsed by CSCO, ISMPO, JSMO, KSMO, MOS and SSO

Abstract: The most recent version of the European Society for Medical Oncology (ESMO) Clinical Practice Guidelines for the diagnosis, treatment and follow-up of hepatocellular carcinoma (HCC) was published in 2018, and covered the diagnosis, management, treatment and follow-up of early, intermediate and advanced disease. At the ESMO Asia Meeting in November 2018 it was decided by both the ESMO and the Taiwan Oncology Society (TOS) to convene a special guidelines meeting immediately after the Taiwan Joint Cancer Conferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
126
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 121 publications
(85 reference statements)
0
126
0
Order By: Relevance
“…In the REFLECT trial, lenvatinib showed noninferiority to sorafenib in overall survival (OS), with a clinically meaningful improvement in progression-free survival (PFS), and objective response rate (ORR) [11]. Current international guidelines recommend lenvatinib as the first-line therapy for patients with advanced HCC [12-15]. Real-world evidence is important in HCC because of the discrepancies in patient characteristics between clinical trials and daily practice.…”
Section: Introductionmentioning
confidence: 99%
“…In the REFLECT trial, lenvatinib showed noninferiority to sorafenib in overall survival (OS), with a clinically meaningful improvement in progression-free survival (PFS), and objective response rate (ORR) [11]. Current international guidelines recommend lenvatinib as the first-line therapy for patients with advanced HCC [12-15]. Real-world evidence is important in HCC because of the discrepancies in patient characteristics between clinical trials and daily practice.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 55 (55%) patients were in the intermediate BCLC stage B and received systemic lenvatinib therapy. The global standard of care recommended for intermediate BCLC stage B is transcatheter arterial chemoembolization (TACE) 38,39 . However, recent clinical studies have shown that lenvatinib treatment for patients with intermediate-stage HCC who present with beyond up-to-seven criteria and have Child-Pugh class A prolonged PFS and OS 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The insidious onset and rapid development of HCC are oen accompanied by the metastasis of cancer cells inside and/or outside the liver, which brings great challenges to the diagnosis and treatment of HCC at the early stage. [3][4][5] Therefore, the development of drug delivery platforms that effectively target tumors, accurately release multi-drugs at desired locations, as well as simultaneously perform diagnosis and treatment has become the focus of cancer research in recent years.…”
Section: Introductionmentioning
confidence: 99%